Relevance of Sulfate Functionalization and Porous Structure of TiO2 Ceramic Foams in Photocatalytic Degradation of Dye Molecules - Moraes, Paula G.P. [UNESP]; Alves-Rosa, Marinalva A. [UNESP]; Santilli, Celso V. [UNESP]; Pulcinelli, Sandra H. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2024)
A one-step route was developed for sulfate functionalization of titania foam, consisting of integrating the sol-gel process with an emulsion template. The resulting material was used to evaluate the relevance of the porous structure and surface sulfate groups in the photocatalytic degradation of Rhodamine B molecules in water under UV irradiation. X-ray diffraction (XRD) analysis showed that the anatase crystalline phase was metastabilized by functionalization of the surface with sulfate species, which caused the crystallite size to decrease from 21 to 10 nm, while the specific surface area increased from 4 to 42 cm2 g-1. Small-angle X-ray scattering (SAXS) measurements during heating of the non-sulfated (E-TiO2) and sulfated (E-TiO2/SO42-) sols emulsified with sodium dodecyl sulfate (SDS) as surfactant and isopropyl myristate as the nonpolar phase, revealed formation of the liquid crystalline structure. Elimination of this mesophase template allowed the preparation of ceramic foams with hierarchical structure formed by meso- and macropore families. The kinetics of photodegradation reaction of Rhodamine B followed a pseudo-first order mechanism. The most efficient photocatalytic activity (higher rate constant and shorter half-life time) was obtained for the foam templated using 20% of SDS (E-TiO2/SO42- 20SDS), which exhibited the highest values for porosity (93%) and specific surface area (80 m3 g-1).
Keywords: ceramic foam; dye photodegradation; emulsion template; sol-gel; sulfated titania